(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Secondary structures of ITS1 and ITS2 transcripts of Atocion hypanicum (Klokov) Tzvelev and A. compactum (Fisch. ex Hornem.) Tzvelev were reconstructed. The presence of a unique nucleotide substitution in fourth helix of A. hypanicum ITS1 transcript, which lead to a disturbance in the secondary structure of the helix, strongly supported it as a separate operational taxonomic unit. The lack of CBC in obtained sequences of ITS2 from A. hypanicum and A. compactum confirmed the absence of genetic barriers for the taxa crossing. Phenotypical distinctions between A. hypanicum and A. compactum from Caucasus associated with bracts and the morphology of the uppermost leaves are demonstrated. The separate species status of A. hypanicum was confirmed.